Ovid, ‘Metamorphoses’ 5,254–6,2, and the Terms for the Muses in Greek and Roman Culture - Mojsik, Tomasz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
Epithets used to describe the Muses are an essential component of metapoetic language, starting as early as the time of Homer and Hesiod. However, it has never been a static phenomenon, as the cultural transformations entailed the changes in the language describing the Muses. Its scope included physical appearance, ancestry, voice/sound, relations with the poet/musician and – a rather important aspect – geographical associations. Revealing traces of this imagery is not an easy task: we lack cult hymns, and in most literary works, we encounter merely 2–3 epithets at the most. In this respect, Ovid is exceptional. In his Metamorphoses (5,254–6,2), in the story of the contest between the Muses of Helicon and the false Pierides, the poet deploys a uniquely rich descriptive terminology concerning the Muses (Mnemonides, Thespiades, Aonides, Emathides, [Pierides], doctae sorores, etc.). In this article, I look at the poet’s choices in this story and analyze the origins, functions and connotations of the epithets and terms he uses.